2014
DOI: 10.1097/meg.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic neuroendocrine tumors

Abstract: Pancreatic neuroendocrine tumors (PNETs) share a unique genetic identity, functional behavior, and clinical course. Compared with tumors of the exocrine pancreas, they are rare and show a different biologic behavior and prognosis. On the basis of data from recent studies, all PNETs, outside of small insulinomas, should be considered potentially malignant and treated accordingly. Untreated tumors have a high possibility to grow locally into adjacent structures or spread to distant organs. Although surgical exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 123 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Traditional chemotherapy is generally ineffective and patient management often encompasses only symptom palliation. 20 Previous studies demonstrated RBP2 overexpression in non-NETs; 19 however, we are the first group to show overexpression of RBP2 in NETs and their metastases. In this study, we identified and quantified RBP2 overexpression in 20 out of 25 human NET samples, or 80% of the tumors measured.…”
Section: Discussionmentioning
confidence: 72%
“…Traditional chemotherapy is generally ineffective and patient management often encompasses only symptom palliation. 20 Previous studies demonstrated RBP2 overexpression in non-NETs; 19 however, we are the first group to show overexpression of RBP2 in NETs and their metastases. In this study, we identified and quantified RBP2 overexpression in 20 out of 25 human NET samples, or 80% of the tumors measured.…”
Section: Discussionmentioning
confidence: 72%
“…Surgical resection is the cornerstone of treatment for localised disease [ 7 , 8 ]. The optimum surgical approach or extent of lymphadenectomy however is uncertain.…”
Section: Discussionmentioning
confidence: 99%